Dissection of the Control of Anion Homeostasis by Associative Transcriptomics in Brassica napus . Issue 1 (21st July 2014) - Koprivova, Anna; Harper, Andrea L.; Trick, Martin; Bancroft, Ian; Kopriva, Stanislav
Abstract : Associative transcriptomics in Brassica napus identified candidate genes for the control of variation in nitrate, phosphate, and sulfate contents . Abstract: To assess the variation in nutrient homeostasis in oilseed rape and to identify the genes responsible for this variation, we determined foliar anion levels in a diversity panel of Brassica napus accessions, 84 of which had been genotyped previously using messenger RNA sequencing. We applied associative transcriptomics to identify sequence polymorphisms linked to variation in nitrate, phosphate, or sulfate in these accessions. The analysis identified several hundred significant associations for each anion. Using functional annotation of Arabidopsis ( Arabidopsis thaliana ) homologs and available microarray data, we identified 60 candidate genes for controlling variation in the anion contents. To verify that these genes function in the control of nutrient homeostasis, we obtained Arabidopsis transfer DNA insertion lines for these candidates and tested them for the accumulation of nitrate, phosphate, and sulfate. Fourteen lines differed significantly in levels of the corresponding anions. Several of these genes have been shown previously to affect the accumulation of the corresponding anions in Arabidopsis mutants. These results thus confirm the power of associative transcriptomics in dissection of the genetic control of complex traits and present a set of candidate genes for use in the improvement of efficiency of B. napus mineral nutrition.